Mn‐loaded apoferritin: a highly sensitive MRI imaging probe for the detection and characterization of hepatocarcinoma lesions in a transgenic mouse model - Geninatti Crich, Simonetta (2012)
Mn-Apo is a highly sensitive MRI contrast agent consisting of ca. 1000 manganese atoms entrapped in the inner cavity of apoferritin. Part of the metallic payload is in the form of Mn2+ ions that endow the nano-sized system with a very high relaxivity that can be exploited to detect hepatocellular carcinoma in mice. Cellular studies showed that Mn-Apo is readily taken up by normal hepatocytes via the ferritin transporting route. Conversely, hepatoma cells (HTC) displayed a markedly reduced ability to entrap Mn-Apo from the culture medium. The i.v. administration of Mn-Apo into C57BL/6 J mice resulted in a marked liver tissue hyperintensity in T1-weighted MR image 20 min after injection. When injected into HBV-tg transgenic mice that spontaneously develop hepatocellular carcinoma (HCC), Mn-Apo allowed a clear delineation of healthy liver tissue and tumor lesions as hyperintense and hypointense T1-weighted MR images, respectively. Immunohistochemistry analysis correlated Mn-Apo cellular uptake to SCARA5 receptor expression. When the MRI contrast induced by Mn-Apo was compared with that induced by Gd–BOPTA (a commercial contrast agent known to enter mouse hepatocytes through organic anion transporters) it was found that only some of the lesions were detected by both agents while others could only be visualized by one of the two. These results suggest that Mn-Apo may be useful to detect otherwise invisible lesions and that the extent of its uptake directly reports the expression/regulation of SCARA5 receptors. Mn-Apo contrastenhanced MR images may therefore contribute to improving HCC lesion detection and characterization.